Contribution of Learning Method and Activities to the Learning Outcomes of Fikih Students at Madrasah Tsanawiyah - Zega, Faris Indra Pratama; Nahar, Syamsu; OK, Azizah Hanum (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The purpose of this study is to determine the impact of learning methods and learning activities on the learning outcomes of fiqh students at a private madrasah tsanawiyah in Gunung Sitoli city. This Research quantitative research method with a correlation research approach was used in this study. This study employs both a population and a sample. This study included four madrasas as participants. Only 72 students from the four madrasahs are included in the population. The sample is comprised of 72 students drawn from the entire population. The study's findings indicate that there is a positive and significant relationship between the application of learning methods and student learning outcomes of Fiqh, which means that the higher and more positive the application of learning methods, the higher and more positive the student learning outcomes, with an effective contribution of 9.90 percent. This means that a variation of 9.90% in the variable application of learning methods can be predicted in terms of improving students' Fiqh learning outcomes.